2005
DOI: 10.1002/app.21578
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microwave and thermal cure of epoxy–anhydride resins: Mechanical properties and dynamic characteristics

Abstract: ABSTRACT:The objective of this work was to compare the mechanical properties of epoxy resins cured by thermal heating and microwave heating. Epoxy-anhydride (100:80) resins were cured in a domestic microwave oven and in a thermal oven. The hardening agents included methyl tetrahydrophthalic anhydride and methyl hexahydrophthalic anhydride. Three types of accelerators were employed. Thermal curing was performed at 150°C for 20 and 14 min for resins containing 1 and 4% accelerator, respectively. Microwave curing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 57 publications
2
18
0
2
Order By: Relevance
“…Since microwaves are of long wavelength, the energy penetrates deeper than ultraviolet or electron-beam irradiation [19]. Further it has many remarkable advantages over conventional heating such as, enhanced reaction rate, higher chemical yield, uniform processing, short reaction time, economically very cheap and clean.…”
Section: Introductionmentioning
confidence: 99%
“…Since microwaves are of long wavelength, the energy penetrates deeper than ultraviolet or electron-beam irradiation [19]. Further it has many remarkable advantages over conventional heating such as, enhanced reaction rate, higher chemical yield, uniform processing, short reaction time, economically very cheap and clean.…”
Section: Introductionmentioning
confidence: 99%
“…However, epoxy resins are one of the most important candidate thermoset due to having excellent electrical insulators, surface coatings, adhesives, and fiber‐reinforced composites. There have been key interests in the area of electromagnetic interference shielding and microwave absorption for epoxy resins, including epoxy–amine systems and epoxy–anhydride systems . L. A. Ramajo et al has reported that, epoxy resins are excellent insulator and protect component from short circuiting.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the case of composites employing thermosetting resins such as epoxy resin, insofar as the curing reaction occurs, the absorption capacity of the microwave, and its conversion into heat, decays considerably. [1] The microwaves are emitted and, as a reflection of the same in the furnace are formed several resonance modes with different points of maxima and minima, resulting in several hot spots, as the intensity of emitted energy. In this work, the heating profiles of these hot and cold spots were studied by infrared thermal images of composites based on glass fiber and epoxy.…”
Section: Introductionmentioning
confidence: 99%